Teachers’ motivation as a mediation mechanism in self-directed learning-conducive primary school environments - Du Toit-Brits, Charlene; Armstrong, Elizabeth-Ann; Blignaut, Henry (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2026)
Although self-directed learning (SDL) is widely recognised as the foundation for learner autonomy and lifelong learning, limited empirical research has examined how teachers’ motivation mediates the cultivation of SDL-conducive learning environments in primary schools. Guided by Self-Determination Theory and Long’s dimensions of SDL (motivation, metacognition, and self-regulation), this qualitative interpretive study explored how teachers' motivation shapes supportive learning environments. Eleven (11) purposively selected primary school teachers from the North-West Province participated in semi-structured face-to-face individual interviews. Data were analysed inductively using thematic analysis. The findings suggest that teachers’ autonomous motivation operates through two interconnected pathways: (1) climate-building teaching practices that foster psychological safety, competence, autonomy and belonging; and (2) lead-by-example modelling that makes goal setting, reflection, and self-monitoring visible to learners. In contrast, lower motivation and limited support were associated with a reversion to more teacher-centred practices that restrict the autonomy of the learner. This study contributes to SDL scholarship by conceptualising teachers’ motivation not as a static trait, but as an enacted professional resource that mediates between instructional design and the development of learner SDL in primary education settings.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Volume 10, Issue 1, 2026
Keywords: Autonomous; Empowered; Intrinsic motivation; Learning environment; Motivation; Self- directed learning; Self-efficacy; Motivation (Psychology); Education, Primary; Independent study; Study skills; Teaching -- Psychological aspects